Social psychology of helping relations : solidarity and hierarchy - Nadler, Arie (Hoboken, NJ : John Wiley & Sons, Inc., 2020)
'Books on the social psychology of helping share a common emphasis on the question of interpersonal help-giving and focus on: Who helps Whom, When and Why. This project will extend this traditional emphasis and consider a wider spectrum of interpersonal and intergroup helping relations. First, in addition to research on the giving of help the book will consider the recipient of help and review research and theory on people's readiness to seek and receive help. Second, it will go beyond the analyses of the immediate helping interaction to consider the long-term consequences of giving and receiving help. Third, the book will highlight that beyond the dichotomy between giving/receiving help or not, there are important implications to different kinds of help (e.g., that encourages dependency or autonomy). Finally, the proposed book will address research and theory on interpersonal and intergroup helping relations'--
Broad perspectives : philosophical and psychological theory, evolution, and overview of social psychological research -- Social psychology of helping relations : when, who, why help-giving -- From help giving to helping relations : consequences of giving and receiving help -- Intergroup helping relations -- Concluding comments.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Helping behavior; Social psychology